Implementation of the Morning Qur’an Recitation Program in Improving Students’ Ability to Read the Quran - Mulia Sopiandi Harahap; Muhammad Suma Hafiz; Nur Azizah (Fakultas Agama Islam, 2026)
The morning Qur’an recitation program is a form of religious habituation aimed at improving students’ ability to read the Qur’an through regular and continuous activities. However, in practice, some students still experience difficulties in reading the Qur’an fluently and correctly, so more targeted efforts are needed to address this issue. This study aims to analyze the implementation of the morning Qur’an recitation program in improving students’ Qur’anic reading abilities at SMP IT Al-Ma’arif NU Pekanbaru. This research employs a qualitative descriptive approach conducted at SMP IT Al-Ma’arif NU Pekanbaru. The research informants consisted of Islamic Education teachers as the main informants, as well as the school principal and students as supporting informants. Data were collected through observation, interviews, and documentation, and analyzed using an interactive model involving data reduction, data display, and conclusion drawing, with validity tested through source and method triangulation.The findings show that the program is implemented regularly with teacher guidance and has a positive impact on improving students’ Qur’anic reading abilities. Supporting factors include program consistency, active teacher involvement, and a religious school environment, while inhibiting factors include differences in students’ abilities, limited instructional time, and low learning motivation. It can be concluded that the morning Qur’an recitation program contributes to improving students’ Qur’anic reading skills and forming their religious habits.